Quality of Sunflower Oil Obtained in the Main Producing Region of Brazil: Adherence to the Codex Alimentarius. (7th March 2019) - de Carvalho, Claudio Guilherme Portela; Mazzola, Luana Fernanda; Caldeira, Andressa; Dalchiavon, Flávio Carlos; Mandarino, José Marcos Gontijo
Abstract: The objective of this work was to evaluate the quality of the oil extracted from sunflower achenes grown in Campo Novo de Parecis, the main producing region of Brazil, to optimize its use by the processing and food industries. In addition, the fatty acid profiles of the oil were checked for their adherence to the CODEX STAN 210–1999. Traditional and high‐oleic genotypes were grown between 2014 and 2017 during trials with a randomized complete block experimental design with four replications. The contents of oleic, linoleic, palmitic, and stearic acids were determined using gas chromatography. The fatty acid profiles of traditional genotypes were observed to be outside the ranges established by the CODEX, with an oleic acid content above 39.4% and linoleic, palmitic, and stearic acid values lower than 48.3%, 2.7%, and 5.0%, respectively, as well as high‐oleic sunflower oil with a stearic acid content of less than 2.6%. The availability of this information can, on the one hand, positively impact industries and encourage the use of better quality raw materials that are more technologically and nutritionally adequate. On the other hand, the commercialization of sunflower oil with a fatty acid profile outside the ranges established by CODEX can be difficult, because the contents are out of specification due to the climatic conditions in the cropping region.